Squamatinia algharbica gen. n. sp. n., a remarkable new Coletiniinae silverfish (Zygentoma: Nicoletiidae) from caves in southern Portugal - Reboleira, Ana Sofia P. S.; Gonçalves, Fernando; Oromí, Pedro; Mendes, Luis F. (Zootaxa, 2012)
A new genus of Coletiniinae silverfish (Nicoletiidae) similar to Coletinia Wygodzinsky and Lepidospora Escherich isdescribed to accommodate the new species Squamatinia algharbica gen. n. sp. n. Many individuals were collected overall seasons of the year in four caves of the Algarve karst massif in the south of Portugal. An identification key for the known genera of Coletiniinae is provided, as well as some biogeographical and ecological comments.